MicroRNAs and ventricular remodeling in aortic stenosis - João Santos-Faria; Cristina Gavina; Patrícia Rodrigues; João Coelho; Paula da Costa Martins; Adelino Leite-Moreira; Inês Falcão-Pires (Revista Portuguesa de Cardiologia, 2020)
Introduction and Objectives: Several mechanisms contribute to myocardial hypertrophy and fibrosis in aortic stenosis (AS). MicroRNAs are post-transcriptional modulators of such processes. We hypothesized that their expression in myocardial biopsies from patients with AS could be linked with the degree of left ventricular (LV) hypertrophy and remodeling and to plasma levels of important biomarkers of extracellular matrix turnover. Methods: We performed myocardial biopsies in eleven patients with isolated severe AS undergoing aortic valve replacement. Echocardiographic exams and biomarker quantification were also performed. Five explanted hearts were used as controls for microRNA expression. Results: Overexpression of microRNA-101-3p was found in AS, which correlated with higher levels of preoperative valvuloarterial impedance, angiotensin II receptor and angiotensin-converting enzyme, and LV mass regression after surgery. Although not differently expressed in AS compared to controls, both upregulation of miR-4268 and downregulation of microRNA-125-5p were associated with higher LV mass. MicroRNA-125b-5p correlated negatively with LV mass and with relative wall thickness at six-month follow-up. MicroRNA-4268 correlated positively with LV mass regression and was associated with higher plasma angiotensin II receptor levels. Conclusions: MicroRNA-101-3p and microRNA-4268 have potential new roles in the modulation of the hypertrophic response to AS via the renin-angiotensin-aldosterone system and as predictors of reverse remodeling after aortic valve replacement. Our results open new avenues in the understanding of myocardial response to pressure overload and of reverse remodeling after unloading. They also support the possibility of medical therapy to modulate the renin-angiotensin-aldosterone system in hypertrophic hearts. Resumo: Introdução e objetivos: Numerosos mecanismos contribuem para hipertrofia e fibrose miocárdica em doentes com estenose aórtica (EA), incluindo modulação pós-transcripcional por microARNs. Levantamos a hipótese da sua expressão em biópsias miocárdicas de doentes com EA relacionar-se com o grau de hipertrofia ventricular esquerda e processos de remodelagem ventricular, bem como com níveis plasmáticos de biomarcadores importantes de turnover da matriz extracelular. Métodos: Realizamos biópsias miocárdicas em 11 doentes com EA grave isolada referenciados para substituição valvular. Executamos também ecocardiografia e quantificação de biomarcadores. Cinco corações explantados foram usados como controlo da expressão dos microARNs. Resultados: Descobrimos uma sobre-expressão do microARN-101-3p em doentes com EA que se correlaciona com níveis mais elevados pré-operatórios de impedância valvuloarterial, recetor tipo 2 da angiotensina (AT2), enzima conversora da angiotensina e regressão da massa ventricular esquerda (MVE) pós-cirurgia. Apesar de não significativamente diferentes entre grupos, descobrimos que sobrerregulação do microARN-4268 e sub-regulação do microARN-125b-5p estão associadas a maior MVE pré-operatória. O microARN-125-5p correlaciona-se negativamente com a MVE indexada e com a espessura relativa da parede aos seis meses de seguimento. O microRNA-4268 correlaciona-se positivamente com a regressão da MVE e associa-se a níveis mais elevados do recetor AT2. Conclusões: Os microARN-101-3p e microARN-4268, via sistema renina-angiotensina-aldosterona, têm potencial novo papel na modulação hipertrófica na EA e como preditores de remodelagem reversa pós-cirurgia. Estes resultados auxiliam na compreensão da resposta miocárdica à sobrecarga de pressão e da remodelagem reversa após diminuição da carga. Suportam também a hipótese de modulação farmacológica do sistema renina-angiotensina-aldosterona em corações hipertróficos.